The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

The role of the SADC Protocol on Trade in Services in regional integration - Swanepoel, L. B. (North-West University, 2018)
Trade in Services can be described as a transaction between a supplier and a consumer without any physical movement of goods across international borders. This, in itself, presents major economic growth possibilities in both regional and multilateral terms. Regional trade agreements, if drafted to suit the specific region's strengths, can promote Trade in Services and establish regional integration. The fact that Trade in Services and regional integration, throughout the Southern African Development Community (SADC) specifically, is moving forward at such a slow pace is due to the lack of political ambition and policy makers failing to emphasise the establishment of trade specific regulatory coherence among member states. Given policy’s impact on Trade in Services, regional trade agreements must be designed to address new and emerging issues that, not only haven't been taken up in previous trade agreements, but which is also region specific and focused enough to build on new standards found in other new trade agreements that will boost regional integration. SADC countries are still in process of establishing a regional services market and, as it currently stands, major development possibilities still exist. This study compares the Trans-Pacific Partnership (TPP) with SADC’s Protocol on Trade in Services (PTIS), with the goal to determine the principles that are necessary to establish a regional market for the integration of Trade in Services. It was found that the PTIS lacks such principles and that integration of services throughout the SADC region is highly unlikely if set forth in its current direction. The finding was that the establishment of regional integration of Trade in Services throughout SADC will have to start with regulatory coherence among its members.
Keywords: Modes of trade; Regional integration; Regulatory coherence; Trade in Services

Does the 1980 Vienna Sales Convention Reflect Universal Values? The Use of the CISG as a Model for Law Reform and Regional Specificities - Schroeter, Ulrich (Loyola of Los Angeles International and Comparative Law Review, 2018)

African Trade Growth or Trade Deficit: GATT/WTO Rules as Trojan Horse on African Trade Development - Obida, Idibia Daniel (World Journal of Research and Review, 2018)
The principle of Most Favored Nation (MFN) as a GATT rule as annexed to World Trade Organisation (WTO) is viewed as very crucial in the operations of the WTO amongst member countries. Another rule of striking importance is the standard of non-discrimination inserted in the MFN rules. As against the background, this study addresses the routine conviction with respect to the viability of GATT laws and WTO rules in the light of non-discrimination principle and Multifibre Agreement (MFA) and, The National Treatment Principle. The study explores the standards of these rules which are whittled down with concrete exemption clauses. These clauses make the adequacy of unhindered commerce guideline perplexed amongst member nations especially, the Sub-Saharan Africa. The study finds that rules of GATT having been made since 1947 at the time when Africa‟s economic development was annexed to their colonial masters and therefore, not in contemplation by the progenitors. The realization that Africa ought to be given chance to develop come too late within the GATT rules. The study finds that the current GATT structure cannot advance the promotion of African trade. The study addresses the grouping of African nations with other nations like Asia, India and South America as a misnomer and erroneous as Africa is the least developed in terms of international trade bargaining power among other developing countries. The study after analyzing MFN, MFA, National Treatment principle and Transparency rules of GATT, concludes they are development deficit as against trade promotion. The study further concludes that the difficulties in finding an acceptable definition of the „like product‟ by several Dispute Resolution Panels as laid down by GATT makes nonsense of the rule and a lacuna in the definition of Article III (2) and III (4) as they are components of paralysis of non-clarifications.
Keywords: GATT; General Agreement on Tariffs and Trade; Most Favoured Nations; Multifibre Agreement; WTO; World Trade Organization

Cross-border contracting: how to draft and negotiate international commercial contracts - International Trade Centre (ITC) (International Trade Centre (ITC), 2018)
Keywords: Iinternational contracts; International sale of goods; UN Convention on Contracts for the International Sale of Goods (1980)

Choice of law in international commercial contracts : a comparative study of Private International Law in Ghana and South Africa - Kwame, Essah (University of Johannesburg, 2018)

Modification of choice of law in the BRICS countries : the role of Article 2(3) of the Hague Principles on choice of law in international commercial contracts - Ndlovu, Docus Sanele (University of Johannesburg, 2018)
Each member state of the BRICS countries is different about the modalities and limitations of party autonomy in their field of Private International law. The principle of party autonomy allows parties to choose the law applicable to their contract and is meant to respect the choice of contracting parties. Since laws are not absolute, they need to change to the needs of a changing society. This can generate a problem in instances where contracting parties have already chosen a choice of law to govern their contract. The question is then whether the governing law of a contract that was previously chosen by the parties can be changed after that contract has been concluded. The scope of party autonomy extends to permitting parties to modify their chosen law in instances where it is necessary to do so, subject to limitations of a specific legal system and principles of conflict of laws. However, the legal rules of each BRICS countries differ in permitting parties to modify the chosen law. This minor dissertation analyses whether the principle of party autonomy is recognised in each member state of the BRICS countries and whether it extends to allow for modification of choice of law. It further asserts that the BRICS countries could plausibly refer to the rules and recommendations of Article 2(3) of the Hague Principles on Choice of Law in International Commercial Contracts to advance the wide acceptance of modification of choice of law. LL.M. (International Commercial Law)

International Trade, Environment and Sustainable Development - Ruppel, Oliver C. (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Issues related to international trade and the environment undoubtedly are of significance to developing countries like Cameroon because they argue that developed countries have depleted resources and indulged in environmentally harmful practices during the past century, in order to achieve unprecedented high standards of living.² The developing countries therefore demand a general but differentiated responsibility, seeking open trade and compensation for adopting environmentally restraining policies.³ Upon further reflection on the link between economic growth activities, environmental protection and social development, the triangular debate on these topics will be highlighted briefly, by introducing the various perspectives.⁴ Trade creates the wealth, which